Targeted-Therapy and Imaging Response: A New Paradigm For Clinical Evaluation? - Milano, Amalia; Perri, Francesco; Ciarmiello, Andrea; Caponigro, Francesco (Reviews on Recent Clinical Trials, 2011)
Clinical management of patients with malignant tumors has dramatically changed over the last years with the introduction of novel therapeutics, such as receptor-targeted therapies, downstream effectors and antiangiogenic compounds. This has created a need to re-evaluate the existing criteria used to assess treatment response. Emerging diagnostic techniques, combining functional and structural data may play a relevant role in planning new treatment strategies in individual cancer patients. In the new scenario where biological treatment results in stable disease, standard Response Evaluation Criteria in Solid Tumors (RECIST) and RECIST 1.1 criteria have limitations. Moreover, functional 18- fluorodeoxyglucose (18FDG)-positron emission tomography (PET) imaging provides an additional tool to assess tumor activity, particularly consistent in some settings, such as Gastro Intestinal Solid Tumors (GIST), hepatocarcinoma, nonsmall lung cancer, and colorectal cancer. The integration of 18FDG-PET and computed tomography (CT) enhances the evaluation of oncologic patients treated with molecularly targeted drugs, and accelerates drug development in many types of tumors.
Keywords: nonsmall lung cancer